MAJOR ELEMENT HETEROGENEITY IN ARCHEAN TO RECENT MANTLE PLUME STARTING-HEADS - Gibson S.A. (My University, 2002)
Variations in the bulk-rock compositions of primary high-Mg melts provide important constraints on the thermal and chemical structure of their mantle source regions. Picrites and komatiites of Archean to Recent age exhibit a wide range of FeO and Al2O3 at a given MgO content. Those with FeO* contents (total Fe as FeO)>12.5 wt% have low Al2O3 contents (typically<10 wt%), and also fractionated heavy rare-earth-element ratios ([Gd/Yb]n=1.25–3.75), that are consistent with melt generation in the garnet-stability field. The high-Fe magnesian melts typically have positive ϵNd values, which are similar or slightly lower than those of co-existing picrites and komatiites, and suggest that the convecting mantle was the predominant melt source region. The high-Fe magnesian magmas typically occur at, or close to, the base of igneous successions of Archean (e.g. Onverwacht Group, S. Africa and Superior Province, Canada) and Phanerozoic age (e.g. Siberia, Paraná-Etendeka, and the North Atlantic Igneous Province) and appear to represent some of the earliest magmas to be generated during melting of mantle plume starting-heads. Generation of high-Fe magnesian melts cannot be readily explained by high-pressure melting of fertile peridotite in a dynamic melting regime. A comparison of the bulk-rock compositions of Fe-rich picrites with the results of recent experimental studies on basalt–peridotite mixtures suggests that the high-Fe magnesian melts may have been generated by moderate amounts of partial melting of ‘re-fertilised’ peridotite at potential temperatures of ≥1450°C and pressures ≥4.5 GPa. This hybrid Fe-rich peridotite is thought to result from a series of progressive mixing and reaction processes between subducted oceanic crust (eclogite) and convecting mantle. These findings suggest that compositional heterogeneity, involving streaks of recycled oceanic crust in a peridotite host, may have been a characteristic of mantle plume starting-heads since Archean times.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей